MED27, SLC6A7, and MPPE1 Variants in a Complex Neurodevelopmental Disorder with Severe Dystonia - Reid, Kimberley M.; Spaull, Robert; Salian, Smrithi; Barwick, Katy; Meyer, Esther; Zhen, Juan; Hirata, Hiromi; Sheipouri, Diba; Benkerroum, Hind; Gorman, Kathleen M.; Papandreou, Apostolos; Simpson, Michael A.; et al. (Movement disorders, 2022)
ABSTRACT Background Despite advances in next generation sequencing technologies, the identification of variants of uncertain significance (VUS) can often hinder definitive diagnosis in patients with complex neurodevelopmental disorders. Objective The objective of this study was to identify and characterize the underlying cause of disease in a family with two children with severe developmental delay associated with generalized dystonia and episodic status dystonicus, chorea, epilepsy, and cataracts. Methods Candidate genes identified by autozygosity mapping and whole‐exome sequencing were characterized using cellular and vertebrate model systems. Results Homozygous variants were found in three candidate genes: MED27, SLC6A7, and MPPE1. Although the patients had features of MED27‐related disorder, the SLC6A7 and MPPE1 variants were functionally investigated. SLC6A7 variant in vitro overexpression caused decreased proline transport as a result of reduced cell‐surface expression, and zebrafish knockdown of slc6a7 exhibited developmental delay and fragile motor neuron morphology that could not be rescued by L‐proline transporter–G396S RNA. Lastly, patient fibroblasts displayed reduced cell‐surface expression of glycophosphatidylinositol‐anchored proteins linked to MPPE1 dysfunction. Conclusions We report a family harboring a homozygous MED27 variant with additional loss‐of‐function SLC6A7 and MPPE1 gene variants, which potentially contribute to a blended phenotype caused by multilocus pathogenic variants. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society